COHESIVE DEVICES IN ENGLISH DEPARTMENT STUDENTS’ RESEARCH ARTICLES - Triana Triana; Amrin Saragih; Marisi Debora (LINGUISTICA, 2019)
This study deals with investigating cohesive devices in English department students’ research articles. This study aims at discovering types of cohesive devices and explaining why they are used in English department students’ research articles. Qualitative content analysis was utilized as a research design in this study. The data were in the form of clauses obtained from introduction part of 5 articles written by English department students. From the data analysis, it was discovered that there are 4 types of cohesive devices found namely reference, substitutions, ellipsis, and conjunction totaling to 593 occurrences with the dominant type is reference totaling to 419 instances (70.66%). The factors affecting the use of cohesive devices are the number of sentences and clauses in the articles. Article with high cohesion tend to have more sentences than the others with middle and low cohesion. The highly cohesive texts employ more cohesive devices because there are more ideas to connect in relation to the number of sentences. Keywords: cohesive devices, research articles, content analysis